THE VALUES OF PANCASILA IN BUSINESS ACTIVITIES IN INDONESIA (CASE STUDIES OF LIMITED LIABILITY COMPANY AND COOPERATION) - Mrs Sulistiowati; Mr Nurhasan Ismail; Mr Paripurna; Mr Sulastriyono (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2016)
This research was conducted to identify the values of Pancasila in business activities with case studies of cooperation and limited liability company in Indonesia. This research is a socio-legal studies that discuss the relationship values of Pancasila as the nation’s philosophy of life and economic law as the legal basis for the development of business activities in Indonesia. The results showed values of Pancasila very relevant to be applied in business activities, most of which have been accommodated in the laws and regulations governing business activities in Indonesia, but there are also some content of value that has not been accommodated. Penelitian ini dilakukan untuk mengidentifikasi tata nilai Pancasila dalam kegiatan usaha dengan studi kasus koperasi & perseroan terbatas di Indonesia. Penelitian ini merupakan kajian sosio-legal yang membahas keterkaitan nilai-nilai Pancasila sebagai falsafah hidup bangsa dan hukum ekonomi sebagai landasan bagi pembangunan hukum kegiatan usaha di Indonesia. Hasil penelitian menunjukkan nilai-nilai Pancasila sangat relevan untuk diterapkan dalam kegiatan usaha, yang sebagian besarnya telah diakomodir dalam peraturan perundang-undangan yang mengatur kegiatan usaha di Indonesia, namun terdapat pula beberapa kandungan nilai yang belum terakomodir.